2019
DOI: 10.3390/s19163497
|View full text |Cite
|
Sign up to set email alerts
|

A Further Exploration of Multi-Slot Based Spectrum Sensing

Abstract: Spectrum sensing (SS) exhibits its advantages in the era of Internet of Things (IoT) due to limited spectrum resource and a lower utilization rate of authorized spectrum. In consequence, the performance improvement of SS seems a matter of great significance for the development of wireless communication and IoT. Motivated by this, this paper is devoted to multi-slot based SS in specialty and several important conclusions are drawn. Firstly, SS with one slot outperforms those with multiple slots if decision fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Moreover, Zhu et al 14 have shown that for the multi‐slot‐dependent cooperative spectrum sensing (CSS), the majority voting mechanism among the several SUs accomplishes the best sensing performance under the decision fusion rule. Furthermore, because of the fading issues of the channel, among the PUs and SUs, the lone SU performance, with the use of an energy detector, is sometimes restricted.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Zhu et al 14 have shown that for the multi‐slot‐dependent cooperative spectrum sensing (CSS), the majority voting mechanism among the several SUs accomplishes the best sensing performance under the decision fusion rule. Furthermore, because of the fading issues of the channel, among the PUs and SUs, the lone SU performance, with the use of an energy detector, is sometimes restricted.…”
Section: Introductionmentioning
confidence: 99%